Energy Efficiency in Commercial Buildings: Challenges, Opportunities, and Solutions (Review) - Vyas Sneha; Sharma Anupama (Journal of Energy Conservation, 2023)
Commercial buildings consume a significant amount of energy, contributing to greenhouse gas emissions and climate change. The adoption of energy-efficient technologies and practices can help reduce energy consumption and lower operating costs while improving occupant comfort and productivity. This research paper aims to explore the challenges, opportunities, and solutions related to energy efficiency in commercial buildings. The paper discusses the current state of energy efficiency in commercial buildings, identifies the key challenges, and highlights the opportunities for improving energy efficiency. The paper also presents the latest energy-efficient technologies and practices, including building automation systems, energy-efficient lighting, HVAC systems, and renewable energy sources. Finally, the paper concludes with recommendations for policymakers, building owners, and managers on how to promote energy efficiency in commercial buildings.
Keywords: Building automation systems (BAS)